Internal and external factors' influence on recycling: insights from a laboratory experiment with observed behavior - Linder, Noah (2022)
Internal psychological factors, such as intentions and personal norms, are central predictors of pro-environmental behavior in many theoretical models, whereas the influence from external factors such as the physical environment is seldom considered. Even rarer is studying how internal factors interact with the physical context in which decisions take place. In the current study, we addressed the relative influence and interaction of psychological and environmental factors on pro-environmental behavior. A laboratory experiment presented participants (N = 399) with a choice to dispatch a used plastic cup in a recycling or general waste bin after participating in a staged "yogurt taste test." Results showed how the spatial positioning of bins explained more than half of the variance in recycling behavior whilst self-reported recycling intentions were not related to which bin they used. Rinsing cups (to reduce contamination) before recycling, on the other hand, was related to both behavioral intention and external factors. These results show that even seemingly small differences in a choice context can influence how well internal psychological factors predict behavior and how aspects of the physical environment can assist the alignment of behavior and intentions, as well as steering behavior regardless of motivation.